The effect of tax training and tax understanding on tax compliance - Fitrini Mansur; Eko Prasetyo; Aulia Beatrice Brilliant; Riski Hernando (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to examine the effect of tax training on MSME taxpayer compliance in the city of Jambi. Then, this study also examines the effect of tax knowledge on the compliance of MSME taxpayers in Jambi City. This study uses a moderating variable of tax sanctions on the relationship between tax training and tax knowledge on taxpayer compliance. The population and sample in this study used compulsory taxation for MSMEs in Jambi City, with the data collected utilizing a questionnaire. The results of this study show that tax training affects SME taxpayer compliance and tax knowledge also affects the compliance of MSME taxpayers, and tax sanctions can moderate the relationship between tax training and tax knowledge on MSME taxpayer compliance in Jambi City. Keywords: Tax Compliance, Tax Training, Tax Understanding, Tax Sanction